Fazendo música juntos: narrativas de integrantes do conjunto de flautas doces da UERGS - Anders, Fernanda (2019)
The present thesis was developed in the Graduate Program in Education of the Federal University of Santa Maria, within the line of Education and Arts research and it is linked to the NarraMus research group. The university structure that makes this venture feasible, articulates teaching, research and extension. Its theme is in the field of Music Education, specifically in the areas of musical practice together and the training of music teachers. The research sought to understand the meaning that licensed or recently licensed musicians attribute to the experience of playing together, guided by the following question: How do life stories affect and are affected by the experience of making music together? Five members of Uergs' Recorder Ensemble participated in the research, including four undergraduate students and a recently licensed musician. The theoretical basis follows the (auto)biographical method, dedicating itself to life histories and formation, starting from Josso (2007, 2008, 2010), Abrahão (2006, 2010, 2011), Abrahão and Bolívar (2014) and Pineau (2006), and the musical practice together and the social relations that are analyzed from Schütz (1979, 2006). With regard to teacher training, we adopted Marcelo García and Vaillant (2012), Nóvoa (1992, 2017), Schön (2000) and Zeichner (1993); Bellochio (2003; 2016) and Penna (2010).The results of this research show three main themes: the first deals with the participants' life context, their childhood experiences and their first contact with the flute; the second is associated with the practice of group music, specifically musical learning and the social relations that flow from it; the third concerns musical experiences in teaching. Life stories were reflected and re-signified on the basis of interpersonal and intersubjective relationships provided by shared group experiences. It was possible to follow the formative process and at the same time constitutive of their identities as individuals and their ethical position as future teachers of music. The production of didactic concerts and the direct approach of the licenciandos and teachers of music with the public formed by students were fundamental opportunities of conscientization on the teaching performance. Analyzes of the narratives produced by the research participants show that the experience of playing together produced meanings that affected the course of their lives, modified impressions about themselves, and broadened themselves as perspectives of professional life. Based on the understanding of the meanings, obtained learning and values shared by the participants of the research, it is accepted that the experience of playing together can promote feelings that ensure the development and the professional formation of the graduating musicians.